The Legal Position of SKMHT (Power of Attorney to Charge Mortgage Rights) in Working Capital Credit Engagements - Sulistyaningrum, Ike; Hadi Prayitno, Ahmad (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2023)
A Power of Attorney to Encumber Mortgage Rights is a letter containing a power of attorney made or given by the collateral provider or business owner, in this case the debtor as the party giving the power of attorney to the creditor as the party receiving the power of attorney to represent the power of attorney in granting mortgage rights to the creditor for the business capital of the power of attorney. . This research is an Empirical Juridical research aimed at finding out and explaining the procedures for making a Power of Attorney to Charge Mortgage Rights (SKMHT) in providing business capital credit facilities at Bank Mandiri, Tegal City, to find out and explain the legal position of a Power of Attorney to Charge Mortgage Rights (SKMHT) in granting credit. business capital at Bank Mandiri Tegal City and to find out and explain the legal consequences of a Power of Attorney Imposing Mortgage Rights (SKMHT) on debtors in default at Bank Mandiri Tegal City. The research approach used in this thesis is an empirical juridical legal research method which relies on primary data (field research) and the research specifications applied in this research are analytical descriptive with a population and the sampling technique used is non-random sampling with purposive sampling. The results of this research indicate that the procedure for making a Power of Attorney to Charge Mortgage Rights (SKMHT) must be made specifically and authentically before a Notary, preceded by the signing of a credit agreement. The position or function of a Power of Attorney to Encumber Mortgage Rights (SKMHT) is as a power of attorney addressed to the holder of mortgage rights or another party to represent the person giving the mortgage rights. In the event that the debtor defaults, the recipient of the power of attorney can proceed with making a Deed of Granting Mortgage Rights so that the creditor is a preferential creditor.